Labour scarcity in Denmark: What role do foreign recruitments play? - Pernille Valentin Borgensgaard (Danmarks Nationalbank, 2022)
Over the coming years, the workingage population of native Danes is expected to fall substantially, and tailwinds from past labour market reforms will, to some extent, die down. As the structural labour force is expected to increase at a slower pace, international recruitments may come to play an even more important role in the Danish labour market. This memo shows that while only a small share of total recruitments come from abroad, foreign labour has contributed markedly to employment growth in Denmark, particularly in industries facing significant labour shortages. The influx of internationally recruited labour is no longer halted by the pandemic, and wage disparities continue to make Danish jobs attractive. Hence, Danish firms still appear to have the option of recruiting workers from abroad when domestic resources are scarce.
Keywords: 330; Personalbeschaffung; Arbeitsmigranten; Arbeitsmarktstatistik; Dänemark